Northern region asplenia register–analysis of first two years. Issue 6 (1st June 1999) - Spickett, G P; Bullimore, J; Wallis, J; Smith, S; Saunders, P
Abstract : OBJECTIVES: To assess the feasibility of setting up a register of patients with asplenia within a defined geographical area; to ensure that guidelines on best practice were implemented; to obtain information on antibody levels to pneumococcal capsular polysaccharides and Haemophilus influenzae type b capsular polysaccharide, before and after immunisation and annually thereafter; to raise awareness of risks among clinicians and to offer advice on management. DESIGN: Prospective recruitment using multiple sources of recruitment. Annual follow up reminders sent from Registration Centre. SUBJECTS: Population of (old, pre-1995) Northern Health Region: approximately 3.1 million. MAIN OUTCOME MEASURES: Data were obtained on reasons for asplenia, duration of asplenia, use of prophylactic antibiotics, Medic-Alert bracelets, immunisations, antibody levels, death. RESULTS: The register was initiated at the beginning of April 1995 and ran to the end of March 1997. After two years of operation, 1111 cases had been registered but the response from some health districts was poor. Major primary causes of asplenia were trauma (264), other surgical (198), lymphoproliferative disease (154), and idiopathic thrombocytopenic purpura (147). There were 664 patients on prophylactic antibiotics, of whom 498 were on continuous antibiotics. Only 18 had any type of warning bracelet. Antibody measurements were carried out at least once on 75% of patients; 306 patients had satisfactory antibody levels on first blood sample in year 1, rising to 405 in year 2; 43 patients failed to make any antibody response to Pneumovax despite multiple immunisations, and three patients failed to respond to Hib vaccine. Sixteen patients with satisfactory antibody levels in year 1 had low levels in year 2 requiring vaccine boosters. Sixteen deaths were reported, two of which were directly attributable to overwhelming sepsis. CONCLUSIONS: Registration has been successful and has raised awareness of the management of asplenia. Compliance with antibiotic prophylaxis and immunisation was initially poor. A potential high risk group of vaccine non-responders has been identified and poor persistence of pneumococcal antibodies has been identified which is likely to alter approaches to immunisation in asplenic patients.